(untitled) (LACCEI, 2024)
Pisco is the denomination of origin of a brandy produced by distilling fresh grape musts from the so-called pisco grapes, harvested on the southern coast of Peru. During the conventional process, a pomace is generated, a mixture of peels and seeds and stem remains, the result of extracting virgin must from the grape as a result of pressing after destemming the grape. In the present work, a process is used that considers the controlled pre-fermentation of the crushed in a reactor equipped with an agitator with also controlled agitation speed, which achieves a greater recovery of must and an effective separation of husks and seeds. The objective of this work is to evaluate the nutrient and functional properties of the peel and seeds separated with the proposed process. For which the shells and seeds were dried in the sun, stored correctly in plastic bags, and then characterized. The proximal analysis of the shells and seeds was measured. In the case of the peels, their functional properties and dietary fiber content, total polyphenol content, anthocyanin content and antioxidant capacity were determined using the ABTS method. In the case of the seed, the oil was extracted, from which its fatty acid profile was determined. The results obtained show that the peels and seeds obtained have a high content of bioactive compounds, dietary fiber and fatty acids, respectively, and have great potential to be used in the food, pharmaceutical and cosmetic industries.